Changes in Coagulation and Fibrinolytic Indices in Women with Polycystic Ovarian Syndrome Undergoing Controlled Ovarian Hyperstimulation. (13th October 2014) - Huang, Ying; Zhao, Yong; Yan, Ling; Chuai, Yun-Hai; Liu, Ling-Ling; Chen, Yi; Li, Min; Wang, Ai-Ming
Abstract : Background . Polycystic ovarian syndrome (PCOS) women undergoing in vitro fertilization and embryo transfer (IVF-ET) treatment always attain a low cumulative pregnancy rate disaccording with the satisfactory number of oocytes. Objective . We aim to evaluate the status of coagulation and fibrinolytic system in PCOS patients undergoing controlled ovarian hyperstimulation (COH) process. Method . Of the 97 women, 30 patients with PCOS composed the study group; 67 women of child-bearing age with normal endocrine function composed the control group. All participants underwent GnRH agonist standard long protocol, and plasma HCY, FVIII, FX, and D-dimer levels as well as hormone parameters were measured at day of full downregulation, hCG priming, and embryos transfer. Results . On day of full downregulation, FX levels were significantly higher in PCOS group (P < 0.01 ). On hCG priming day, FX and estrogen levels in PCOS group were higher than in the control group and FVIII levels were significantly lower on day of embryos transfer whereas FX and E2 levels were significantly higher in PCOS group. Conclusion . Hypercoagulable state during peri-implantation phase would probably lead to poor microcirculation of endometrium and be one of the most important disadvantages of successful implantation and subsequent clinical pregnancy.